WhatsApp Health Education and Its Effect on Antenatal Visit Motivation Among Mothers at Buntut Bali Health Center - Meldawati , Metri Wiyayuni; -, Meldawati; Rahman, Luthfia Hidayati (Sahabat Publikasi Kuu, 2025)
Background: Pregnant women's examinations must be carried out periodically at least 6 times during pregnancy. Whether or not health services for pregnant women are achieved can be seen from the scope of K1, K4 and K6. Pure K1 is the first contact of pregnant women with health workers during the first trimester of pregnancy. Pregnant women should do pure K1, so that if there are complications or risk factors, they can be found and treated as early as possible. Research objective: To determine the effect of health education via WhatsApp (WA) on maternal motivation in pregnancy visits at the Buntut Bali Health Center. Research Method: The type of research used in this study is an experiment with a one group pre-test-post-test design. The population in this study were all pregnant women registered at the Buntut Bali Health Center in 2024 and the number of samples was 30 samples and the statistical test used was the Wilcoxon test. Research results: The results of statistical tests using the Wilcoxon test show that the P value is 0.001 < a 0.05, meaning there is an effect of health education via WhatsApp (WA) on maternal motivation in pregnancy visits Conclusion: Health education through videos via WhatsApp (WA) has an impact on the motivation of mothers in antenatal visits.